The measurement of the Entrepreneurial Orientation in family firms: a critical review of the literature - Arzubiaga, Unai; Iturralde, Txomin; Maseda, Amaia (European Journal of Family Business, 2012)
The present paper makes a deep review of the Entrepreneurial Orientation construct analyzing the specific case of family firms. A classification of the works that contain a model where EO plays two different roles has been done: on the one hand, works where this construct has been taken as a dependent variable and, on the other hand, papers where it has been understood as an independent variable. With the purpose of analizying the EO construct in a great depth, a literature review of each five dimensions has been done, focusing on the specific case of family firms. Joining to these dimensions, it has been done an examination of how the EO construct has been measured, focusing on two of the most accepted trends: measuring it with a three dimension scale or doing it with a five dimension one. Finally, we made a reflection about which of these scales is more appropriate for the specific case of family firms justifying our position.